Endoscopic follow-up of low-grade precancerous bronchial lesions in high-risk patients: long-term results of the SELEPREBB randomised multicentre trial. Issue 3 (15th September 2022) - Guisier, Florian; Deslee, Gaëtan; Birembaut, Philippe; Escarguel, Bruno; Chapel, Françoise; Bota, Suzanna; Métayer, Josette; Lachkar, Samy; Capron, Frédérique; Homasson, Jean Paul; Taulelle, Marc; Quintana, Marie; et al.
Background: 3–9% of low-grade preinvasive bronchial lesions progress to cancer. This study assessed the usefulness of an intensive bronchoscopy surveillance strategy in patients with bronchial lesions up to moderate squamous dysplasia. Methods: SELEPREBB (ClinicalTrials.gov NCT00213603) was a randomised study conducted in 17 French centres. After baseline lung computed tomography (CT) and autofluorescence bronchoscopy (AFB) to exclude lung cancer and bronchial severe squamous dysplasia or carcinoma in situ (CIS), patients were assigned to standard surveillance (arm A) with CT and AFB at 36 months or to intensive surveillance (arm B) with AFB every 6 months. Further long-term data were obtained with a median follow-up of 4.7 years. Results: 364 patients were randomised (A: 180, B: 184). 27 patients developed invasive lung cancer and two developed persistent CIS during the study, with no difference between arms (OR 0.63, 95% CI 0.20–1.96, p=0.42). Mild or moderate dysplasia at baseline bronchoscopy was a significant lung cancer risk factor both at 3 years (8 of 74 patients, OR 6.9, 95% CI 2.5–18.9, p<0.001) and at maximum follow-up (16 of 74 patients, OR 5.9, 95% CI 2.9–12.0, p<0.001). Smoking cessation was significantly associated with clearance of bronchial dysplasia on follow-up (OR 0.12, 95% CI 0.01–0.66, p=0.005) and with a reduced risk of lung cancer at 5 years (OR 0.15, 95% CI 0.003–0.99, p=0.04). Conclusion: Patients with mild or moderate dysplasia are at very high risk for lung cancer at 5 years, with smoking cessation significantly reducing the risk. Whereas intensive bronchoscopy surveillance does not improve patient outcomes, the identification of bronchial dysplasia using initial bronchoscopy maybe useful for risk stratification strategies in lung cancer screening programmes. Intensive bronchoscopic surveillance of low-grade precancerous bronchial lesions does not improve outcomes. Mild/moderate dysplasia defines a very high-risk group for invasive lung cancer. Smoking cessation is highly effective even in this group. https://bit.ly/3L3xrgU